2017
DOI: 10.1177/1087054717713638
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Occurrence of Autism Spectrum Disorder in Children With ADHD

Abstract: Objective Children with attention-deficit/hyperactivity disorder (ADHD) frequently present with autism spectrum disorder (ASD) symptomatology, yet there is a notable gap in the treatment needs of this sub-population, including whether the presence of ASD may be associated with more severe ADHD symptoms. Method Data from the 2014 National Survey of the Diagnosis and Treatment of ADHD and Tourette Syndrome (n=2,464) was used to compare children diagnosed with ADHD and ASD to children with ADHD, but not ASD. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 46 publications
7
58
3
3
Order By: Relevance
“…Variations in ADHD prevalence rates have been identified between US and non-US studies (Faraone et al, 2003). As shown in Table 3, US studies (Grzadzinski et al, 2011;Kotte et al, 2013;Reiersen et al, 2007;Salley et al, 2015;Grzadzinski et al, 2016;Zablotsky et al, 2017) were identified to have a similar random pooled effect size to non-US studies (Ronald et al, 2008;Kochhar et al, 2011;Lichtenstein et al, 2010;Russell et al, 2014;Craig et al, 2015;Green et al, 2015;Jensen and Steinhausen, 2015). High levels of heterogeneity were identified in both US studies (78.61%) and non-US studies (89.86%), with US studies contributing to more of the heterogeneity.…”
Section: Us V Non-us Studiesmentioning
confidence: 93%
“…Variations in ADHD prevalence rates have been identified between US and non-US studies (Faraone et al, 2003). As shown in Table 3, US studies (Grzadzinski et al, 2011;Kotte et al, 2013;Reiersen et al, 2007;Salley et al, 2015;Grzadzinski et al, 2016;Zablotsky et al, 2017) were identified to have a similar random pooled effect size to non-US studies (Ronald et al, 2008;Kochhar et al, 2011;Lichtenstein et al, 2010;Russell et al, 2014;Craig et al, 2015;Green et al, 2015;Jensen and Steinhausen, 2015). High levels of heterogeneity were identified in both US studies (78.61%) and non-US studies (89.86%), with US studies contributing to more of the heterogeneity.…”
Section: Us V Non-us Studiesmentioning
confidence: 93%
“…Similar to other NDs, like autism spectrum disorder (ASD), ADHD symptoms typically have their onset during childhood and tend to persist into adolescence and adulthood (Thapar, Cooper, & Rutter, ). In addition, individuals diagnosed with ADHD often present with symptoms or a diagnosis of other NDs, including learning disability (Koolwijk et al., ; Larson, Russ, Kahn, & Halfon, ), language problems (Korrel, Mueller, Silk, Anderson, & Sciberras, ; Larson et al., ), ASD (Grzadzinski, Dick, Lord, & Bishop, ; Koolwijk et al., ; Larson et al., ; Zablotsky, Bramlett, & Blumberg, ), and intellectual disability (ID; Faraone, Ghirardi, Kuja‐Halkola, Lichtenstein, & Larsson, ). ADHD is also associated with several risky behaviors and adverse health outcomes (Balazs & Kereszteny, ; Erskine et al., ; Mohr‐Jensen & Steinhausen, ; Nigg, ), including injuries (Ruiz‐Goikoetxea et al., ), which represent a leading cause of morbidity and mortality among children (Haagsma et al., ; WHO, ).…”
Section: Introductionmentioning
confidence: 99%
“…Children diagnosed with both ASD and ADHD had greater treatment needs, more co-occurring conditions, and were more likely to have a combined hyperactive/impulsive and inattentive ADHD subtype [9]. This may be one of the reasons for patients with ADHD in our study to have a longer mean hospitalization stay.…”
Section: Discussionmentioning
confidence: 86%